Documentary research on social innovation in health in Latin America. - Castro-Arroyave, D. M.; Duque-Paz, L. F. (Infectious Diseases of Poverty, 2020)
Background: Identifying social innovation in health initiatives, promoting quality of life through them, and transforming current health conditions demand the knowledge, comprehension and appropriation of the theoretical and methodological developments of this concept. Academic developments in social innovation have mainly occurred in and been documented for English-speaking countries, although...
Publisher: BioMed Central Ltd
Keywords: Amérique latine; Innovation sociale; Libre accès; Santé